2003
DOI: 10.1136/vr.152.13.387
|View full text |Cite
|
Sign up to set email alerts
|

Detection of disease‐specific PrP in the distal ileum of cattle exposed orally to the agent of bovine spongiform encephalopathy

Abstract: The immunohistochemical localisation of the disease-specific protein, PrP(Sc), was examined in the distal ileum of cattle up to 40 months after they had been exposed orally to the agent of bovine spongiform encephalopathy (BSE), in the intestines and mesenteric lymph nodes of an additional group of cattle, killed six months after a similar exposure, and in the distal ileum of naturally occurring clinical cases of BSE. PrP(Sc) was detected, mainly in macrophages, in a small proportion of the follicles of Peyer'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
136
1
3

Year Published

2004
2004
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(144 citation statements)
references
References 33 publications
4
136
1
3
Order By: Relevance
“…The Peyer's patches in the distal ileum of the cattle were one of the most possible sites on PrP Sc neuroinvasion [30]. As the Peyer's patches are localized in the antimesenteric wall of the ileum, HRP was injected into the intestinal wall in the antimesenteric side of the distal ileum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Peyer's patches in the distal ileum of the cattle were one of the most possible sites on PrP Sc neuroinvasion [30]. As the Peyer's patches are localized in the antimesenteric wall of the ileum, HRP was injected into the intestinal wall in the antimesenteric side of the distal ileum.…”
Section: Discussionmentioning
confidence: 99%
“…The distal ileum is one of the most possible sites on prion neuroinvasion, because it is an early detection site of PrP Sc accumulation following the oral prion challenge in the cattle [30]. Via sympathetic, parasympathetic and sensory nerves, PrP Sc may be transported from the ileum to the spinal cord and brain.…”
mentioning
confidence: 99%
“…The infectivity levels in lymphoid tissues greatly vary depending on the prion agent or strain type [12]. Some scrapie strains, the CWD and vCJD agents are able to replicate in such tissues [2,178,200] whereas accumulation of BSE prions in cattle is only evidenced in the terminal ileum, in experimental infection yet not in natural cases [191]. Intriguingly, a prion agent can become lymphotropic upon interspecies transmission, as seen for BSE in sheep [75] or vCJD in humans [200].…”
mentioning
confidence: 99%
“…PrP sc accumulates mainly in the specified-risk material, such as brain, spinal cord and dorsal root ganglion, and it has been suggested that PrP sc may be transmitted from distal ileum or tonsil to peripheral nervous system and then invade into central nervous system. However, PrP sc deposition has been also reported in peripheral tissues of BSE cattle [2][3][4][5] . In the 94-month-old cow infected with PrP sc , protease A-resistant prion protein was found in peripheral nervous system such as ischiadic nerve and in adrenal gland 6) .…”
Section: Introductionmentioning
confidence: 99%